Quasi-Equilibrium Problems and Fixed Point Theorems of Separately l.s.c and u.s.c Mappings. (25th January 2018) - Xuan Tan, Nguyen
ABSTRACT: In this paper, we apply our new results on quasi-variational inequality problems to generalized quasi-equilibrium problems. Some suﬃcient conditions on the existence of solutions are shown. In particular, we establish several results on the existence of solutions to fixed points of separately lower and upper semicontinuous (lower and lower, upper and upper) mappings.These generalize some well-known fixed point theorems obtained by previous authors as Browder and Ky Fan, Wu, et al., etc.